DAMPAK PENGGUNAAN GADGET DENGAN BIMBINGAN ORANGTUA TERHADAP HASIL BELAJAR SISWA KELAS 3 MI AL-HUDA PLOSO - Lestari, Yuni Widya; Astuti, Efi Tri (INSTRUKTUR INSTRUKTUR: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
One example of technological advancement in the era of society 5.0 is the existence of a gadget. Gadgets have quite an influential impact on children. When there is no control or control in the use of gadgets, children will be out of control because gadgets can now be connected to the internet which can access freely. Departing from this problem, this study aims to examine the impacts of gadget use and parental efforts to control gadget use on grade 3 students of MI Al-Huda, Ploso, Pacitan Regency. This study uses a quantitative research method, namely research using numerical or statistical data to analyze the observed phenomena. The results of this study indicate that the use of gadgets with parental guidance has a very positive impact on the learning outcomes of grade 3 students of MI Al-Huda Ploso, Pacitan Regency, , namely students can improve their learning outcomes and reduce the level of addiction to playing gadget